2009
DOI: 10.1001/archneurol.2008.567
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Brain Atrophy in Benign vs Early Multiple Sclerosis

Abstract: Background: Benign multiple sclerosis (MS) is defined by minimal or no disability after many years of observation, therefore a less degenerative disease process is suspected to be present in this subset of patients. Objective: To compare brain atrophy rates in patients with long-standing benign MS vs typical early MS. Design: A longitudinal prospective cohort study and a retrospective database review. Setting: An academic MS center. Patients: Thirty-nine patients with clinically defined benign MS and an age-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…In line with previous observation, 11,21 our findings confirm that a low cortical lesion burden is a main feature of patients having the benign MS course. Indeed, despite the huge difference in disease duration, the benign MS group was characterized by significantly lower CL number and volume, percentage of patients having CLs and number of gadolinium-enhancing CLs, as compared to the RRMS group.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous observation, 11,21 our findings confirm that a low cortical lesion burden is a main feature of patients having the benign MS course. Indeed, despite the huge difference in disease duration, the benign MS group was characterized by significantly lower CL number and volume, percentage of patients having CLs and number of gadolinium-enhancing CLs, as compared to the RRMS group.…”
Section: Discussionsupporting
confidence: 93%
“…Other investigations have demonstrated that T2 lesion load and presence of baseline gadolinium-enhancing lesions on MRI are the greatest predictors of disability and clinical course (43-44). Conversely, while brain atrophy has been found to be less severe among patients with benign MS (16), similar or greater degrees of RNFL loss were seen in our study and are likely reflective of the higher incidence of ON with its inherent visual pathway-specific axonal degeneration. Although patients with benign MS may experience less difficulty with ambulation by definition based on their EDSS, they have reduced QOL scores not only for vision but for overall aspects of physical functioning.…”
Section: Discussionsupporting
confidence: 75%
“…[2325] In contrast the T2 lesion volume ranked highly amongst predictors of progressive patients, indicating that accrual of lesions, and possibly relapses plays an important role in short-term and possibly long-term disability accrual as has been shown in other studies. [2628].…”
Section: Discussionmentioning
confidence: 84%